2018
DOI: 10.1002/asia.201800307
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Applications of Transition‐Metal‐Catalyzed C−P Bond Cleavage

Abstract: The wide occurrence of carbon-phosphorus bond activation in modern organic synthesis, catalyst deactivation, and biological process has attracted interest for synthetic applications. Over the past few decades, transition-metal-mediated transformations have become extremely powerful tools in organic synthesis. In this review, considerable progress that has been made in catalytic activations and transformations of carbon-phosphorus bonds within the coordination sphere of transition metals is described. Mechanist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 78 publications
0
20
0
Order By: Relevance
“…Consequently,aplausible mechanism was proposed for the reaction of 1b and 2b (Scheme 4b). Thei nitial chemoselective reaction of 2b and Pd(PPh 3 ) 4 produces the expected p-allylpalladium complex A.The dissociated PPh 3 attacks 1b to favorably generate the E-configured allylic P-ylide species B.T hus,t he g-regioselective allylic alkylation occurs by cooperative catalysis.N ext, the key oxidative addition between olefin-complexed Pd 0 and phosphonium groups in C (Pd-decompelxed cation was detected by HRMS analysis) delivers the intermediate D. [14] Therefore,t he classical Heck coupling proceeds to afford the intermediate E,and produce the observed 3b after areductive b-elimination process.Thus, PPh 3 acts as an unusual catalyst in the Pd-catalyzed Hecktype coupling by forming active phosphonium species with 1b,rendering the current reaction proceed by unprecedented auto-tandem cooperative catalysis.…”
Section: B Ut Gave An Inseparablementioning
confidence: 99%
“…Consequently,aplausible mechanism was proposed for the reaction of 1b and 2b (Scheme 4b). Thei nitial chemoselective reaction of 2b and Pd(PPh 3 ) 4 produces the expected p-allylpalladium complex A.The dissociated PPh 3 attacks 1b to favorably generate the E-configured allylic P-ylide species B.T hus,t he g-regioselective allylic alkylation occurs by cooperative catalysis.N ext, the key oxidative addition between olefin-complexed Pd 0 and phosphonium groups in C (Pd-decompelxed cation was detected by HRMS analysis) delivers the intermediate D. [14] Therefore,t he classical Heck coupling proceeds to afford the intermediate E,and produce the observed 3b after areductive b-elimination process.Thus, PPh 3 acts as an unusual catalyst in the Pd-catalyzed Hecktype coupling by forming active phosphonium species with 1b,rendering the current reaction proceed by unprecedented auto-tandem cooperative catalysis.…”
Section: B Ut Gave An Inseparablementioning
confidence: 99%
“…Recently Duan and coworkers reported a protocol that provides an unprecedented intramolecular catalytic aryl phosphination of the internal alkyne with a Pd(OAc)2/CuI bimetallic catalyst system via P-C bond activation of stable tertiaryphosphines (Scheme 21) [58]. The authors indicated that both the lone pair on the phosphine and the alkynyl group tethered to aryl group of the phosphine are crucial for this reaction, and coordination of Pd species with 2-(arylethynyl)phenylphosphine (12) gives a bidentate palladium complex (13). When they tried the intermolecular reaction as a control reaction, no reaction between PPh3 and diphenylacetylene was observed under same reaction conditions.…”
Section: Scheme 20mentioning
confidence: 99%
“…Transition metal-catalyzed phosphine decomposition has been observed in several instances. Earlier studies have been thoroughly reviewed in previous literature [7][8][9][10][11][12][13]. Among the many known deactivation pathways, Garrou indicated that P-C bond scission is an ubiquitous phenomenon observed with a large number of transition metals and phosphine ligands that often lead to a fatal catalyst deactivation through the irreversible formation of phosphido-bridged di and multi-nuclear complexes [7].…”
mentioning
confidence: 99%
“…This process was initially recognized as challenging in the following aspects: 1) It requires the formation of a strained three membered cyclic intermediate; 35,36 2) C-P bond cleavage has never been achieved in the classical Staudinger reaction. In general, C-P bond cleavage normally requires the assistance of metal catalyst and/or base additive, so the feasibility of this step under mild conditions is unknown; [37][38][39][40][41][42][43] 3) Product stability issues: some molecules bearing the N-P (III) bond are unstable and not isolable. 16,44 In this study, by using acyl-phosphine type substrates, we achieved a new Staudinger strategy which is able to maintain the N-P (III) bond and construct the amide bond simultaneously.…”
Section: Introductionmentioning
confidence: 99%